Hard Graft: Collaborative exploration of working class stories in shaping female educator identities - Gillaspy, Emma Elizabeth; Routh, Fiona; Edwards-Smith, Amy; Pywell, Samantha; Luckett, Alison; Cottam, Sheena; Gerrard, Sabina (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
This empirical qualitative study investigates the ways in which working-class roots have shaped educator values and identity. Using collaborative autoethnography, we share an honest insight into the stories of seven female educators drawn together from a variety of health and social care disciplines. The five themes emerging from this research: Connection through differences and commonalities; graft; inner tensions; authenticity ‘I am who I am’ and the bigger picture are tightly interconnected, generating a complex and rich picture of contemporary female educator identity. This supportive and collaborative approach has been transformational in the realisation we are not alone, and it has provided a space to celebrate our ‘otherness’. As a result, we have embraced our collective responsibility to challenge inequalities and foster a more open, accessible and authentic HE future for all.